Racism and Xenophobia in Society, Education, and Sport Settings - Patsiaouras, Αστέριος (Inquiries in Physical Education and Sport, 2008)
This review focuses on racism and xenophobia in society, education and particularly in sport settings. Racism and xenophobia phenomenon is not recently discovered rather it exists many decades now. However, due to the situation that has been shaped in Europe and particularly in Greece by the immigratory waves, racism emerged as a major issue that needs to be solved by the European Community. Education can help the new generation to understand and promote the social values of equality, isonomy, etc. Especially physical education has an important role to play in the transmission of such values through movement and games that create a unique way of non-verbal communication without the linguistic difficulties produced by different languages and culture. Using programs such as ‘‘Kallipateira’’ each physical educator is in position to develop and facilitate the inclusion of children with different color, language or social origin through their participation in physical activities.